2021
DOI: 10.2166/wst.2021.358
|View full text |Cite
|
Sign up to set email alerts
|

Selective adsorption of phosphate by carboxyl-modified activated carbon electrodes for capacitive deionization

Abstract: Capacitive deionization (CDI) has been considered as a promising technology for removing phosphate from water but suffer inferior selectivity and electrosorption performances for phosphate of current carbon electrodes in CDI. Herein, we achieved highly selective phosphate removal from a ternary effluent of Cl−, , and by using nitric acid-treated activated carbon (AC) with various modification times and pure AC as the anode and cathode, a novel phosphate selective asymmetric CDI reactor. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…15−18 A recent study of recovering P using CDI reported a PAC of 1.21 mg P/g electrode (activated carbon). 19 Besides the low adsorption capacity of activated carbon, the co-ion expulsion effect further reduced its PAC. 20 To address these limitations, guanidiniumfunctionalized polyelectrolyte-coated carbon nanotube (Gu-PAH/CNT) electrodes were fabricated to selectively extract phosphate ions due to stronger electrostatic and hydrogenbond forces between the ions and electrode interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15−18 A recent study of recovering P using CDI reported a PAC of 1.21 mg P/g electrode (activated carbon). 19 Besides the low adsorption capacity of activated carbon, the co-ion expulsion effect further reduced its PAC. 20 To address these limitations, guanidiniumfunctionalized polyelectrolyte-coated carbon nanotube (Gu-PAH/CNT) electrodes were fabricated to selectively extract phosphate ions due to stronger electrostatic and hydrogenbond forces between the ions and electrode interface.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional CDI consists of two activated carbon electrodes and a feed chamber formed between the electrodes. , During CDI operation, charged species are captured and adsorbed through the electrical double layer (EDL) established on the electrode surface under an applied electrical potential . Many research studies have explored CDI as a device for P removal, and a common understanding reached is that the P adsorption capacity (PAC) of activated carbon electrodes in CDI is limited and requires improvement. A recent study of recovering P using CDI reported a PAC of 1.21 mg P/g electrode (activated carbon) . Besides the low adsorption capacity of activated carbon, the co-ion expulsion effect further reduced its PAC .…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanum-based adsorbents have been successfully employed in diverse water sources, including freshwater bodies, industrial effluents, and wastewater. Their versatility makes them suitable for a range of applications where phosphate removal is a priority [23]. In the 3-6 pH range, the La-phosphate complex was found to be stable, with no phosphate release or solubility products detectable.…”
Section: Introductionmentioning
confidence: 99%